Proyeksi Produksi Komoditas Pertanian melalui Pendekatan Indeks Location Quotient (LQ) di Kabupaten Malang - Ahmadinah Al Qurni; M. Zul Mazwan; Wahid Muhammad Shodiq (Jurnal Ilmiah Membangun Desa dan Pertanian, 2025)
The agricultural sector in Malang Regency plays a strategic role in boosting local economic productivity. This increase in productivity can influence demand levels, community income, and market competitiveness. This, in turn, can improve community welfare, which can be realized through demand across all economic sectors, both leading and non-leading sectors. This study aims to (1) analyze the leading or base sectors in Malang Regency, and (2) analyze productivity projections for agricultural commodities in Malang Regency. This study was conducted in 2023-2024 using a quantitative descriptive approach. The data used in this study are secondary data obtained from the Central Statistics Agency (BPS) of Malang Regency and East Java Province from 2013 to 2023. The research variables include (X1) GRDP at the Malang Regency level; (X2) GRDP at the East Java Province level; (X3) horticultural production; and (X4) plantation production. The analysis methods used in this study are (1) Location Quotient (LQ) analysis to analyze leading sectors in Malang Regency (objective 1); and (2) trend analysis to project leading agricultural commodities in Malang Regency (objective 2). The study results indicate six leading sectors in Malang Regency, with agriculture being one of the leading sectors, and primary commodities consisting of bananas, sugarcane, and coffee. These three agricultural commodities are projected to experience a positive trend over the next five years (2024-2029). Banana production in 2024 is projected to increase by 14,322.0 quintals from the previous year, reaching 17,887.0 quintals in 2029. Sugarcane production in 2024 is projected to reach 2,877.7 tons and grow to 4,231.3 tons in 2029. Meanwhile, coffee productivity in 2024 is 19.55 tons, rising to 24.98 tons by 2029.